Tributação como instrumento de regulação socioeconômica para a promoção do desenvolvimento nacional - Câmara, Delano Carneiro da Cunha (2019)
It is undeniable the lack of State existing models which is increasing the current political and economic crisis, including in Brazil. On this scenario, the present thesis analyses how taxation could contribute to boost national development and income distribution between social classes. This paper purpose is to look into how the current Brazilian taxation system makes unfeasible the economic development. It aims at to show that not only the indirect taxes promote inequality, but also all types and distribution of tax charges, regarding all social economic segments, lead the country to the underdevelopment. This research aims at to study the interference due to taxation, which sets the national development, limitedly. It is analyzed, specifically, the weight of the taxation charges regarding all social economic segments. It is intended to demonstrate where and how the regressive Brazilian taxation system is leading to the underdevelopment, and by what means it could be modified resulting in the creation of a virtuous circle. This paper's theoretical guideline is based on Thomas Piketty’s literature, highlighting the taxation model that aims to reduce inequality. Following, it will be analyzed the theoretical developmentalists, Celso Furtado, as well as Bresser Pereira, speculative global capitalism critics, Avelã Nunes and Hyman Minsky, and Endorsed doctrinators regarding the economic analysis of the Law, fundamental duty of taxes payments, and the efficient costing of the Constitutional State, Casalta Nabais and Canotilho. The research adopts a deductive approach, technique based on the bibliographic review, empiric quests as of recognized scientific worth from national and foreign private institutions and data from official sites. In conclusion, as an alternative to the regressive Brazilian taxation system that leads to underdevelopment, it is offered a society regulation model which aims at the development and inequality reduction, as a result to better redistribution of the tax charges. It is defended the State costing reinforcement by means of resources from finance transactions taxation.